2009
DOI: 10.1210/me.2009-0010
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Krüppel-Like Factor 5 Expression by Androgens Results in Increased CXCR4-Dependent Migration of Prostate Cancer Cellsin Vitro

Abstract: Advanced prostate cancers preferentially metastasize to bone, suggesting that this tissue produces factors that provide a suitable microenvironment for prostate cancer cells. Recently, it has become clear that even in antiandrogen-resistant cancers, the androgen receptor (AR)-signaling axis is required for prostate cancer progression. Therefore, we hypothesized that AR may be involved in the regulation of pathways that are responsible for the homing of prostate cancer cells to select microenvironments. In supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 57 publications
7
83
1
Order By: Relevance
“…Moreover, cycloheximide did not affect DHT-mediated induction of KLF5 mRNA level, suggesting that KLF5 was a primary responsive gene of androgen. In consistent with our present results Frigo et al (2009), previously reported a direct induction of KLF5 mRNA expression by R1881, synthetic androgen, in a prostate cancer cell line (LNCaP). They also identified putative ARE in first intron of KLF5 gene.…”
Section: K Takagi Et Al: Klf5 In Breast Carcinomasupporting
confidence: 94%
See 2 more Smart Citations
“…Moreover, cycloheximide did not affect DHT-mediated induction of KLF5 mRNA level, suggesting that KLF5 was a primary responsive gene of androgen. In consistent with our present results Frigo et al (2009), previously reported a direct induction of KLF5 mRNA expression by R1881, synthetic androgen, in a prostate cancer cell line (LNCaP). They also identified putative ARE in first intron of KLF5 gene.…”
Section: K Takagi Et Al: Klf5 In Breast Carcinomasupporting
confidence: 94%
“…pKLF5-ARE-Luc and pPSAE-Luc plasmids). At first, pKLF5-ARE-Luc plasmids were constructed to examine possible recruitment of AR into putative androgen-responsive element(s) (ARE) in first intron of KLF5 gene identified by Frigo et al (2009). Briefly, 158 bp DNA region containing ARE within was amplified by PCR method using adapter primers (forward 5 0 -TAGGTACCTCAGTGGATACAAGGTTTTGC-3 0 and reverse 5 0 -TATAAGCTTCGATGCAAACCTT-TAAAATATTGC-3 0 ).…”
Section: Luciferase Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Strikingly, however, a number of the top 20 genes uniquely regulated by cyclin D1b are functionally associated with altered cell migration, invasion, or differentiation, including NTN4, CXCR4, and SNAI2 (Table 1). Of these genes, only CXCR4 and SNAI2 have been shown to be regulated by androgens (16,26). Moreover, comparison of the cyclin D1b-specific gene set (cluster 3) with a recently identified metastasis-associated gene signature across multiple cancer types uncovered commonalities between the 2 gene sets (Supplemental Figure 1D), with SNAI2 as the top cyclin D1b-regulated gene present in this signature (whereas no overlap was seen with the cyclin D1a, cluster 2, gene set).…”
Section: Cyclin D1b Induces a Unique Gene Expression Program Associatmentioning
confidence: 99%
“…Recent findings implicating AR in the regulation of processes associated with metastasis heightened the importance of assessing Slug function in the context of ARpositive tumor cells (26). It is important to note that while the vast majority of metastatic human PCa retains AR, none of the AR-positive model systems reliably spontaneously metastasize in immunocompromised mice (44,45).…”
Section: Slug Enhances Prometastatic Phenotypes Of Pca Cells In Vivomentioning
confidence: 99%